2009
DOI: 10.1038/modpathol.2008.148
|View full text |Cite
|
Sign up to set email alerts
|

TCL1A expression delineates biological and clinical variability in B-cell lymphoma

Abstract: The assembly of a collection of gene-expression signatures of the major types of B-cell non-Hodgkin's lymphoma has identified increased T-cell leukemia/lymphoma 1A (TCL1) expression in multiple lymphoma types and cases, and has enabled the investigation of the functional and clinical importance of TCL1 expression. Specifically, Burkitt's lymphoma cases show a homogeneously strong expression of TCL1, whereas diffuse large B-cell lymphoma, follicular lymphoma, mantle cell lymphoma, chronic lymphocytic leukemia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 33 publications
6
48
1
Order By: Relevance
“…It has been previously described that TCL1 shows a differential and regulated expression pattern in B-CLL (5). Different groups of investigators have observed association of high protein levels of TCL1 with features of aggressive disease in B-CLL (6,7). These results indicate that deregulation of TCL1 is critically important in the pathogenesis of the aggressive form of B-CLL (3).…”
Section: Introductionsupporting
confidence: 53%
“…It has been previously described that TCL1 shows a differential and regulated expression pattern in B-CLL (5). Different groups of investigators have observed association of high protein levels of TCL1 with features of aggressive disease in B-CLL (6,7). These results indicate that deregulation of TCL1 is critically important in the pathogenesis of the aggressive form of B-CLL (3).…”
Section: Introductionsupporting
confidence: 53%
“…24,25 We have previously described that TCL1 shows a differential and regulated expression pattern in CLL, 20 and an association of high protein levels of TCL1 with features of aggressive disease in CLL has been subsequently indicated by us and others. 20,26,27 We show here that the growth stimulatory effects of BCR engagement in CLL cultures are strongly correlated with the levels of TCL1 and the kinetics of TCL1-AKT recruitment to BCR membrane complexes. Increased TCL1 levels are also strongly associated with inferior clinical outcome, independent of treatment.…”
Section: Introductionmentioning
confidence: 86%
“…None of the studies were confirmatory in nature, and those are the only ones in which clinical application can be found. Schreck et al [75] demonstrate that a large number of Th2 cells in HL is related to better survival; Dong et al [76] show that bcl10 expression (next to t (11;14)) is related to HP-eradication unresponsiveness; according to Wang et al [77], cytoplasmic sox11-expressing MCLs have a poorer survival; mutation nor polymorphism of the CD20 gene is predicting rituximab response (Sar et al [78]); Aktas et al [79] show that high apoptotic index is related to good prognosis in pediatric lymphomas; Lenz et al [80] describes new gene signatures that predict therapy response in DLBL; Peh et al [81] found that bcl-6 expression is associated with poor survival in DLBL and immunohistochemically determined ABC not; according to Johnson et al [82], DLBL with low CD20 expression have lower survival rate; Ki67 and Pim1 are independent indicators of poor survival in MCL (Hsi et al [83]); low Ki67 is a negative predictor of survival in DLBL (Hasselblom et al [84]); SIRT1 expression is associated with poor prognosis in DLBL (Jang et al [85]); in FL, Johnson et al [86] show that secondary genetic alterations indicate aggressive behavior; Hasselblom et al [87] show that the number of CD68-positive cells in DLBL does not predict prognosis; TCL1A is associated with more aggressive clinical behavior in CLL and MCL according to Aggarwal et al [88]; aberrations in the MYC locus are associated with poor outcome in DLBL (Klapper et al [89] and Yoon et al [90]); expression of P-glycoprotein indicates therapy unresponsiveness in nasal type NK/T cell lymphoma according to Wang et al [91];…”
Section: Prognostic Factors In Lymphomamentioning
confidence: 99%